PENGGUNAAN METODE ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS V SD - Restio Sidebang (Universitas Quality, 2020)
The research carried out is a classroom action research (PTK) using the Role Playing method in social studies subjects. This study aims to determine the increase in learning outcomes using the Role Playing method in the Social Studies Subject of Class V SD Negeri 040448 Kabanjahe for the 2019/2020 academic year. The location of this research is SD Negeri 040448 Kabanjahe. The subjects of this study were all students of grade V SD Negeri 040448 Kabanjahe, totaling 30 students and the object of this study was the use of the Role Playing method to improve student learning outcomes on the subject of services and roles of warrior figures in preparing for Indonesian independence. The instruments used were student observation and multiple choice tests.The results of the research in cycle I were obtained, namely 18 students who completed (60%), 12 students who did not complete (40%), and an average score of 62.6 had not reached the KKM score of 70. Cycle II action with student results 26 students (86.67%) completed, 4 students who did not complete (13.33%), and an average score of 78.66 can be said to be classically complete because it has reached ≥85%.Based on the results of data analysis, it is concluded that using the Role Playing method can improve student learning outcomes in the social studies subject on the subject of services and the role of warrior figures in preparing for Indonesian independence in class V SD Negeri 040448 Kabanjahe for the 2019/2020 academic year with an increase of 25.5%.